Activities carried out in support of the implementation of the Vienna Programme of Action for Landlocked Developing Countries for the decade 2014-2024 (UN New YorkUS, 2018)
Provides a description of UNCTAD-wide activities in support of the implementation fo the Programme of Action since its adoption in 2014. Includes lessons learned and a way forward for the further implementation of actions and commitments withing the mandate and competence of the UNCTAD.
Keywords: LANDLOCKED COUNTRIES